A Direct Proof of the Integral Formulae for the Inverse Hyperbolic Functions. (1st September 2016) - Engbers, John; Hammett, Adam
Summary: In the same vein as a Classroom Capsule of Arnold Insel on the arctangent, we present a direct geometric derivation of the integral formulae for the inverse hyperbolic functions. We then use these formulae to obtain the derivatives of the various hyperbolic trigonometric functions.